2022
DOI: 10.1002/hsr2.697
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment, perceived medication adherence, and high‐risk medication use in patients with reduced kidney function: A cross‐sectional analysis

Abstract: Background and Aims: Reduced estimated glomerular filtration rate (eGFR < 60 ml/ min/1.73 m 2 ) is a risk factor for cognitive impairment (CI) and medication nonadherence. However, the association between CI and medication adherence in adults with reduced eGFR has not been adequately examined. Our pragmatic objectives were to assess the cross-sectional relationship between CI and selfreported medication adherence, medication number, and use of potentially high-risk medications among adults with reduced eGFR.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…Cognitive dysfunction affects domains such as memory, executive function, attention, orientation, visuospatial ability, and language ability. Thus, it is not surprising that at least part of the relevance of CKD-associated cognitive dysfunction relies on lower treatment compliance [43] along with the worse quality of life experienced by these patients. In this sense, very recent studies have reported apathy symptoms in patients with CKD and lower scores in terms of physical function, social and emotional function, and mental health, among other parameters [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction affects domains such as memory, executive function, attention, orientation, visuospatial ability, and language ability. Thus, it is not surprising that at least part of the relevance of CKD-associated cognitive dysfunction relies on lower treatment compliance [43] along with the worse quality of life experienced by these patients. In this sense, very recent studies have reported apathy symptoms in patients with CKD and lower scores in terms of physical function, social and emotional function, and mental health, among other parameters [24,44].…”
Section: Discussionmentioning
confidence: 99%